Emotional Intensity Modulates the Integration of Bimodal Angry Expressions: ERP Evidence - Pan, Zhihui; Liu, Xi; Luo, Yangmei; Chen, Xuhai (Frontiers in Neuroscience, 2017)
Integration of information from face and voice plays a central role in social interactions. The present study investigated the modulation of emotional intensity on the integration of facial-vocal emotional cues by recording EEG for participants while they were performing emotion identification task on facial, vocal, and bimodal angry expressions varying in emotional intensity. Behavioral results showed the rates of anger and reaction speed increased as emotional intensity across modalities. Critically, the P2 amplitudes were larger for bimodal expressions than for the sum of facial and vocal expressions for low emotional intensity stimuli, but not for middle and high emotional intensity stimuli. These findings suggested that emotional intensity modulates the integration of facial-vocal angry expressions, following the principle of Inverse Effectiveness (IE) in multimodal sensory integration.